Program Development of Religiosity Culture: Improving Educator’s Personality at Madrasa Jabal An-Nur Al-Islamic - Permata Sari, Herdiyas Putri; Junaidi, Junaidi (Universitas Islam Negeri Raden Intan Lampung, 2024)
This type of research is qualitative with a descriptive approach, the data sources in this study are from various sources, namely: madrasa head, vice head, staff, teachers and students. Data collection techniques and instruments through observation, interviews and documentation. Data validity test using source tringulation. The results showed that 1) Implementation of the socialization of religious values through moral education and religious activities. The success of moral education can be seen from the improvement of students' morals and discipline, with supporting factors such as teacher cooperation, religious culture in the community, and parental support. Time and budget limitations are inhibiting factors. 2) Implementation of the weekly Action Plan determination through management functions. Madrasa Jabal An-Nur Al-Islami Bandar Lampung implements planning, organizing, implementing and controlling educational services. Supporters include the existing human resources and the madrasa principal's ability to manage them. 3) Implementation of rewards through planning and implementation. The madrasa principal plays a role in planning, implementing, and shaping the character of educators and students. Madrasas also display learners' work and upload learners' activities to social media. Constraints include the large number of learners, preparation of equipment, limited teacher observation, and lack of guidelines in giving rewards.